Hubungan Pola Makan dengan Kejadian Hipertensi pada Lansia di Puskesmas Sukatani Depok - Jesica Julyana Hutapea; Linda Riski Sefrina; Ratih Kurniasari (Peneliti.net, 2022)
Hypertension is a degenerative disease that is often referred to as the silent killer because people with hypertension do not know if they have hypertension. The cause of hypertension in the elderly generally comes from the condition of the blood vessels. Hypertension is mostly suffered by the elderly age group because with age, the arteries will become harder and inelastic. There are many factors related to the incidence of hypertension, one of which is due to diet, diet is a way to regulate the type or amount of food in order to maintain health, nutritional needs and prevent disease. The purpose of this study was to determine whether there is a relationship between diet (sodium, fat and potassium) on the incidence of hypertension in the elderly. This study uses a cross-sectional research method, this research is a qualitative study whose data were obtained by using FFQ questionnaires and interviews. Respondents in the study amounted to 156 people aged over 60 years with hypertension who visited the Sukatani Health Center. This study showed that there was a significant relationship between sodium and fat consumption and the incidence of hypertension as indicated by p value = 0.009 for sodium consumption and p value = 0.018 for fat consumption, while there was no significant relationship between potassium consumption and the incidence of hypertension in the elderly. indicated by p value = 0.157 with an error rate of 5% or 0.05. Therefore, it is important for the elderly to maintain their diet to prevent the incidence of hypertension.